2009
DOI: 10.1111/j.1469-7610.2009.02101.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of toddlers with ASD: short‐term diagnostic and cognitive outcomes

Abstract: Background Despite recent increases in the number of toddlers referred for a differential diagnosis of autism spectrum disorders (ASD), knowledge of short-term stability of the early diagnosis as well as cognitive outcomes in this cohort is still limited. Method Cognitive, social, and communication skills of 89 clinic-referred toddlers were assessed at the average age of 21.5 (SD = 4.9) months, and reassessed at 46.9 (SD = 7.7) months. Groups with stable and unstable diagnostic presentation were identified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
153
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 187 publications
(170 citation statements)
references
References 50 publications
11
153
1
3
Order By: Relevance
“…10,11 However, the stability of subtype diagnoses within the autism spectrum is more variable. For instance, Chawarska et al 9 found that the stability of autism and PDD-NOS was 74% and 83%, respectively, compared with 100% for the entire category of ASDs; van Daalen et al 12 found that the stability of autism and PDD-NOS was 63% and 54%, respectively, compared with 91% for the entire category of ASDs. Direction of diagnostic changes within the ASD spectrum differs across studies, with some samples showing more movement from PDD-NOS to autism 10 and others showing more movement from autism to PDD-NOS.…”
Section: Index Termsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 However, the stability of subtype diagnoses within the autism spectrum is more variable. For instance, Chawarska et al 9 found that the stability of autism and PDD-NOS was 74% and 83%, respectively, compared with 100% for the entire category of ASDs; van Daalen et al 12 found that the stability of autism and PDD-NOS was 63% and 54%, respectively, compared with 91% for the entire category of ASDs. Direction of diagnostic changes within the ASD spectrum differs across studies, with some samples showing more movement from PDD-NOS to autism 10 and others showing more movement from autism to PDD-NOS.…”
Section: Index Termsmentioning
confidence: 99%
“…[9][10][11][12] As the number of children identified as having ASDs is growing over time, it is important to explore factors associated with change in classification from ASD to non-ASD to inform early identification and intervention efforts. For all ASDs, the stability of an ASD diagnosis between 2 and 4 years of age has been reported to be as high as 91% to 100%, 9,12 and the stability of an ASD diagnosis between 2 and 9 years of age has been reported to be 88% to 90%. 10,11 However, the stability of subtype diagnoses within the autism spectrum is more variable.…”
Section: Index Termsmentioning
confidence: 99%
“…Other conducted studies have also shown that family engagement ensures that therapeutic goals are enhanced in the household, providing a greater synchronicity and both communicative and social between children and their interlocutors (2)(3)(4)(5)(6)(7)(8)(15)(16)(17)(18)(19)(20) . We note that in the first six months of the study, the extent and speed of the evolutionary process became more evident, especially in the TG group, both in the total values of the ABC, and in the separate areas that comprise it.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have stressed the importance of assistance for families due to the severe disturbance in the relational dynamics that takes place because of the impairment in mental and emotional development of their children, which limits the creation and maintenance of reciprocity conditions between the child and his family (14)(15)(16)(17)(18)(19)(20) . Other conducted studies have also shown that family engagement ensures that therapeutic goals are enhanced in the household, providing a greater synchronicity and both communicative and social between children and their interlocutors (2)(3)(4)(5)(6)(7)(8)(15)(16)(17)(18)(19)(20) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation